ARTIFICIAL INTELLIGENCE IN ENGLISH-UZBEK TRANSLATION: BENEFITS AND CHALLENGES - Kuvondikova Shaydo Toʻlqinovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Artificial Intelligence (AI) has become one of the most influential technologies in the field of translation studies. Modern machine translation systems such as Google Translate, DeepL Translator, and ChatGPT are increasingly used for translating texts between different languages, including English and Uzbek. This article examines the advantages and disadvantages of AI-assisted translation in the context of English-Uzbek language pairs. The study analyzes the effectiveness of machine translation tools in terms of speed, accessibility, accuracy, and linguistic adaptation. At the same time, the research investigates the major problems of AI translation, including semantic inaccuracies, mistranslation of idioms, cultural misunderstandings, and grammatical inconsistencies. The article is based on comparative linguistic analysis and translation studies methodology. Scientific observations demonstrate that AI significantly simplifies the translation process and saves time for users; however, it still lacks human creativity, contextual understanding, and cultural sensitivity. The research highlights that English and Uzbek belong to different language families and possess distinct grammatical structures, which creates additional challenges for machine translation systems. The findings indicate that AI can serve as an effective supportive tool for translators, but it cannot completely replace professional human translation. The article also emphasizes the growing role of artificial intelligence in modern linguistics and translation studies and discusses future prospects for improving AI translation technologies for low-resource languages such as Uzbek.